ATAC-seq protocol for the profiling of chromatin accessibility of in situ fixed quiescent and activated muscle stem cells - Anqi Dong; Indigo T.C. Chan; Tom H. Cheung (STAR Protocols, 2023)
Summary: Chromatin accessibility is critical for cell identity. Conventional ATAC-seq can examine chromatin accessibility on freshly prepared muscle stem cells or satellite cells (SCs); however, isolating SCs in mice remains challenging. Here, we present a protocol to preserve the in vivo chromatin profile of SCs by applying paraformaldehyde (PFA) perfusion throughout the mouse before SC isolation. We describe steps for PFA perfusion and FACS sorting of SCs. We then detail library preparation for ATAC-seq.For complete details on the use and execution of this protocol, please refer to Dong et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.